Benthic and Pelagic Contributions to Primary Production: Experimental Insights From the Gulf of Trieste (Northern Adriatic Sea) - Cibic, Tamara; Baldassarre, Laura; Cerino, Federica; Comici, Cinzia; Fornasaro, Daniela; Kralj, Martina; Giani, Michele (Frontiers in Marine Science, 2022)
Although the 14C-method remains one of the most sensitive measures of primary production in marine ecosystems, few data from coastal sublittoral areas are available. We applied an integrated approach to quantify the benthic (PPs) and pelagic (PPw) contributions to total primary production (PPt) in a 17-m deep coastal site. From March 2015 to March 2019, we carried out 16 in situ experiments on a seasonal basis, at the LTER site C1, whereas benthic rates were estimated in the laboratory. To relate PP to seawater physical features and to the water column stability, the Brunt-Väisälä frequency was calculated. We further related our PP rates to the abundance, biomass, main taxonomic groups and diversity of eukaryotic phytoplankton and microphytobenthos (MPB). In November 2018, the maximum PPw (6.71 ± 0.82 µgC L-1 h-1) was estimated at the surface layer, in correspondence to the highest value of dinoflagellates biomass (29.35 µgC L-1), on the account of small (<20 µm) naked and thecate forms. PPi, integrated over the water column, displayed the highest values in July 2017 and July 2018. In sediments, negative PPs values were estimated in late autumn/winter, when minima of MPB abundance occurred. The highest rates were displayed in January 2018 and October 2016 (28.50 and 17.55 mgC m-2 h-1), due to the presence of dominant diatoms Paralia sulcata and Nitzschia sigma var. sigmatella, respectively. The PPs contribution to PPt was negligible (<2%) in 6 out of 16 experiments, with a mean value of 11.3% (excluding negative PPs values) over the study period, while it reached up to 43% in January 2018. The principal component analyses revealed that nutrients availability affected the seasonal development of pelagic and benthic phototrophs and primary production more than the physical variables, except for the surface layer of the water column where temperature and salinity were the main drivers. Our results add on the limited database on primary production in sublittoral areas and represent one of the few attempts, on a global scale, of integrating pelagic and benthic primary production using the 14C method to quantify the overall ecosystem productivity.